2022
DOI: 10.1128/mra.01204-21
|View full text |Cite
|
Sign up to set email alerts
|

Complete Coding Sequence of Lumpy Skin Disease Virus Isolated from Kinmen Island, Taiwan, in 2020

Abstract: We reported the complete coding sequence of a lumpy skin disease virus (LSDV) isolated from cattle from Kinmen, Taiwan, in 2020. The nucleotide sequence of LSDV/KM/Taiwan/2020 was most closely related to strains from an outbreak in China and Vietnam in 2020 and clustered within the vaccine or vaccine-derived clade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…From 2017 to 2019, unusual vaccine-like LSDV strains were detected in diseased cattle in Kazakhstan [52] and in neighbouring regions of Russia [26,27] and China [53,54]. Not much later, similar recombinant LSDV strains were found in Taiwan [35], Vietnam [34,55] and Hong Kong [32]. Whole-genome sequencing showed that the two most likely parental strains were a Neethling-like strain (major parent) and a KSGP-like strain (minor parent) [56,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2017 to 2019, unusual vaccine-like LSDV strains were detected in diseased cattle in Kazakhstan [52] and in neighbouring regions of Russia [26,27] and China [53,54]. Not much later, similar recombinant LSDV strains were found in Taiwan [35], Vietnam [34,55] and Hong Kong [32]. Whole-genome sequencing showed that the two most likely parental strains were a Neethling-like strain (major parent) and a KSGP-like strain (minor parent) [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Whole-genome sequencing (WGS) analyses have shown that the LSDV strains from the 2015–2016 epidemics in south-eastern Europe, Kazakhstan and Russia are most similar to a strain isolated in Israel in 2012 [ 28 , 29 , 30 , 31 ]. In contrast, most of the recent LSDV strains from Russia and Asia appear to be vaccine-like recombinant strains carrying genetic signatures from both Neethling- and KSGP-based LSDV vaccines [ 26 , 32 , 33 , 34 , 35 ]. It is noteworthy that while the use of homologous LSDV vaccines is not authorised in Russia, the Lumpivax vaccine (KEVEVAPI) was used in Kazakhstan shortly before the emergence of the vaccine-like strains [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, LSD was endemic to the African continent; however, the disease has now spread to the Middle East, Europe, and Asia ( 1 ). In 2019, LSD was first reported in Asia and the Pacific region (Bangladesh, China, and India) and then spread to affect Taiwan, Myanmar, Vietnam, Thailand, and Hong Kong territory ( 2 7 ). Here, we report the coding-complete genome sequence of an LSDV strain that was isolated from an LSDV-infected cow during the first LSDV outbreak in Thailand in 2021.…”
Section: Announcementmentioning
confidence: 99%
“…Kenyan strains have caused outbreaks in Kenya, but however never been reported in subsequent epidemics in Africa, the Middle East, and Europe (Tulman et al, 2001). Since 2017, recombinant LSDV strains have been detected in infected cattle in Russia (Sprygin et al, 2018;Sprygin et al, 2020;Shumilova et al, 2022); Krotova et al, 2022a), China (Ma et al, 2021), Hongkong (Flannery et al, 2021), Taiwan (Huang et al, 2022) and Vietnam (Mathijs et al, 2021;Tran et al, 2021). In phylogenetic analysis, recombinant strains formed four monophyletic groups R1, R2, R3, and R4 as described in section 3.3.…”
Section: Phylogenetic Analysismentioning
confidence: 99%